A systems engineering approach to metallurgical accounting of integrated smelter complexes - Mtotywa, Busisiwe Percelia; Lyman, G. J. (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD)--Stellenbosch University, 2008.